The Contribution of Work Values, Career Adaptability, and Willingness to Compromise on Students' Work Readiness during the School-to-Work Transition - Humaira Mustika; Afdal Afdal; Megaiswari Biran Asnah; Nurfarhanah Nurfarhanah (Universitas Ahmad Dahlan, 2024)
Work readiness is a reflection of an individual's quality of life evaluation, viewed from their own perspective. However, in reality, the work readiness of students is still low. This study aims to determine the contribution of work value, career adaptability, and willingness to compromise on students' work readiness during the school-to-work transition. The study uses a descriptive quantitative approach with a correlational method. A total of 210 students were selected through incidental sampling techniques to participate in this research. The instruments used include scales for work value, career adaptability, willingness to compromise, and work readiness. The results of the study indicate that students' work value is in the high category, their career adaptability is in the high category, their willingness to compromise is in the high category, and their work readiness is in the medium category. The findings show that work value, career adaptability, and willingness to compromise significantly contribute positively to students' work readiness. This research implies that future studies should focus on helping students develop work readiness during their school-to-work transition.